The choice of auxiliary substances to obtain sublingual glycin tablets with thiotriazoline with direct compaction method Reporting 1. Study of the influence of excipients on the bulk density, the bulk density after shrinkage, the fluidity and the angle o - L. I. Kucherenko; O. V. Khromylova; H. R. Nimenko; Z. B. Moriak (Zaporozhye State Medical University, 2020)
Today in Ukraine, stroke remains the second and most common cause of premature mortality and disability. More than 111.000 new cases of stroke occur every year in Ukraine. This is a very topical medical and social problem worldwide. Today, a promising area of primary neuroprotection in cerebral ischemia is to correct the imbalance of excitatory and inhibitory neurotransmitter systems through the activation of natural inhibitory processes. Our attention was drawn to the natural inhibitory neurotransmitter glycine and its role in the mechanisms of acute cerebral ischemia. There is evidence of the ability of the thiotriazoline antioxidant to potentiate the therapeutic effect of neurometabolic cerebroprotectors. Based on this, we have created a new combination drug based on glycine with thiotriazoline. For the new combination drug, a rational dosage form of the tablet was selected. The purpose of this work is to select excipients for producing glycine tablets with thiotriazoline by direct compression, to study their effect on bulk density, bulk density after shrinkage, fluidity, and angle of natural inclination. Materials and methods. The studies were used: glycine (manufacturer: China); Thiotriazoline (manufacturer: State Enterprise Chemical Reagents Plant of the Institute of monocrystals of the NAS of Ukraine), certified excipients based on microcrystalline cellulose, granulated sugars, granulated inorganic salts, lubricating as well as domestic. At first, morphometric studies of glycine powders, thiotriazoline, and mixtures of glycine with thiotriazoline were conducted. In the course of the work, four groups of excipients, factors, and their levels were studied. To study the four qualitative factors, we used the Greek-Latin square 4 × 4. The bulk density, the bulk density after shrinkage, the fluidity, and the angle of the natural slope of the glycine powder masses with thiotriazoline were studied. Results. According to the results of the experimental studies, the variance analysis of the experimental data was carried out and conclusions were drawn about the influence of the studied factors on the quality parameters of the glycine powder masses with thiotriazoline Conclusions. In the course of the researches, the influence of four groups of excipients on the bulk density, the bulk density after shrinkage, the fluidity, the angle of the natural slope of the glycine powder masses with thiotriazoline were studied. According to the results of the analysis of variance, optimum auxiliaries were selected which provide quality according to the studied parameters.